The Oxford handbook of the Bronze Age Aegean (ca. 3000-1000 BC) - Cline, Eric H. (Oxford University Press, 2010)
Part I. Background and definitions -- Part II. Chronology and geography. Early Bronze Age ; Middle Bronze Age ; Late Bronze age -- Part III. Thematic topics. Art and architecture ; Society and culture ; Seals and writing/administrative systems ; Material crafts ; Events -- Part IV. Specific sites and regions. Crete ; Mainland Greece ; Cyclades, Dodecanese, and Saronic Islands ; Wider Mediterranean
Literaturangaben
Keywords: Aegean Sea Region -- Antiquities; Aufsatzsammlung; Ausgrabung; Bronzezeit; Ägäis; Vor- und Frühgeschichte